PENDAMPINGAN KELOMPOK GURU DALAM PENGGUNAAN APLIKASI SMART SENYUM UNTUK DETEKSI DINI SEHAT MENTAL SISWA - Nawindah, Nawindah (Jurnal Abdi Insani, 2024)
Sanggar Kegiatan Belajar (SKB) 26 Bintaro is a non-formal educational institution that organizes catch-up learning activities for package A, package B and package C. Various problems faced by students affect teaching and learning activities, such as students rarely attending school, students' lack of motivation. learning, families who do not support the learning activities of children with various conditions certainly really need better treatment. SKB 26 Bintaro does not have a guidance and counseling teacher, so this is a problem that needs to be addressed by various parties. For this reason, it is necessary to detect students' mental health by providing teacher or homeroom teacher assistance in using the Smart Smile application for early detection of students' mental health. Administrators can use the Smart smile application. Teachers and students have knowledge of the importance of mental health. Teachers can accompany students in using the Smart Smile application to determine their mental health level so that the goals of teaching and learning activities can be realized. Preparation consists of preparing material, time, place and the teacher who will be the admin. Providing material on the importance of early detection of mental health, using the Smart Smile application, doing practice, participants working on practice questions. The results of this activity are depicted in graphical form as well as activity evaluation. Administrators of the Smart Smile application can help teachers and students in using it by entering data on students, teachers, counselors and leaders first. Teachers can accompany students in carrying out early detection of mental health with the mental health knowledge provided. Recommendations from the results of early detection of mental health can be used as a tool for treating students. Leaders can see the results of early detection of mental health through reports. There were 75% of participants who understood and were able to use the Smart Smile application menu very well. Regarding understanding and use of the consultation schedule, 63% have good understanding and assessment, so they can provide mental health knowledge to students with the help of the application.